2022
DOI: 10.3389/fmars.2022.986993
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the variation of failure probability of upgraded rubble-mound breakwaters due to climate change

Abstract: The effects of climate change on coastal areas are expected to significantly influence the risk for port operations. In the present work, a novel methodology for the quantitative assessment of the performances of upgraded rubble-mound breakwaters under a changing climate is proposed. For each considered upgrading option, the failure probability related to a certain limit state is calculated through the implementation of Monte Carlo (MC) simulations, using the factor of change (FoC) method to include the projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…In the present work, a marine climate emulator has been employed to generate random sea storms and sea levels, also considering the effects of climate change (Stagnitti et al, 2022). Present (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, a marine climate emulator has been employed to generate random sea storms and sea levels, also considering the effects of climate change (Stagnitti et al, 2022). Present (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, the standard deviation of the Normal distribution of β„Ž π‘€π‘Žπ‘™π‘™ was set following the indications of Lara et al (2019). The employed values of 𝑓, π‘Ž and 𝑏 are not only the ones indicated by van der Meer (1988a) and EurOtop ( 2018), but also the sitespecific ones deduced from the results of the previously carried out composite modeling of the upgraded Catania harbor breakwater (Stagnitti et al, 2020(Stagnitti et al, , 2022(Stagnitti et al, , 2023. In particular, site-specific values of 𝑓 were calculated for the cases showed in Fig.…”
Section: Case Studymentioning
confidence: 99%
“…But if the foreshore becomes steeper because of erosion, then a front berm will also be needed. Stagnitti et al (2022) introduced a novel methodology based on the calculation of the failure probability during a lifetime due to independent failure modes. Their method was employed to evaluate the performance of upgraded breakwaters in response to climate change.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Stagnitti et al [2] demonstrated that traditional formulas for the prediction of mean wave overtopping discharge may fail in representing the hydraulic response of non-conventional damaged and upgraded rubble-mound structures, with estimates up to 300 times higher and 0.9 times lower than the observed values for low and highenergy sea states, respectively. As a consequence, the use of traditional formulations for the probabilistic assessment of the performances of damaged and upgraded rubble-mound breakwaters may cause under or over-estimation of the failure probability of the structure due to excessive mean wave overtopping discharge by up to 70% [3].…”
Section: Introductionmentioning
confidence: 99%